TERAPI BERMAIN PASIR KINETIK (KINETIC SAND) UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK DI TK CINTA KASIH SINTANG - Mulyadi, Yohanes Berkhmas; Suryameng, Suryameng Suryameng; Lorentina, Lorentina Lorentina; Priskylla, Priskylla Priskylla (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study was motivated by the presence of children whose fine motor skills had not yet developed optimally, as indicated by difficulties in holding pencils properly and writing within lines. The study aimed to describe the use of kinetic sand play therapy in improving children’s fine motor skills at TK Cinta Kasih Sintang. This research employed a descriptive qualitative approach. The subjects were selected using purposive sampling and consisted of teachers and children at TK Cinta Kasih Sintang. Data were collected through observation, in-depth interviews, and documentation. Data analysis involved data reduction, categorization, data display, and conclusion drawing. The results showed that teachers implemented kinetic sand play therapy through various activities, such as molding sand using available molds or cake molds, drawing and writing on sand, building sandcastles, and hiding objects in the sand for children to find by digging. However, several challenges were identified, including limited instructional time, low parental awareness of the benefits of kinetic sand play, lack of parental knowledge on how to create kinetic sand at home, and limited availability of materials provided by teachers. In conclusion, kinetic sand play therapy can support the development of children’s fine motor skills, although its implementation requires greater support from both teachers and parents.